2021
DOI: 10.7554/elife.67397
|View full text |Cite
|
Sign up to set email alerts
|

HIV status alters disease severity and immune cell responses in Beta variant SARS-CoV-2 infection wave

Abstract: There are conflicting reports on the effects of HIV on COVID-19. Here we analyzed disease severity and immune cell changes during and after SARS-CoV-2 infection in 236 participants from South Africa, of which 39% were people living with HIV (PLWH), during the first and second (beta dominated) infection waves. The second wave had more PLWH requiring supplemental oxygen relative to HIV negative participants. Higher disease severity was associated with low CD4 T cell counts and higher neutrophil to lymphocyte rat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 78 publications
1
44
1
3
Order By: Relevance
“…Further information on the levels and types of antibodies and the role of T-cells in preventing infections, reducing serious disease or deaths in vaccinated individuals requires definition. In many parts of the world, HIV infection and other infections can synergize with the SARS-CoV-2 influencing COVID-19 management outcomes potentially influencing both pathogenesis of COVID (Karim F et al 2021;Nachega et al 2021b;Nachega et al 2021c).…”
Section: Major Knowledge Gaps On Voc Omicronmentioning
confidence: 99%
“…Further information on the levels and types of antibodies and the role of T-cells in preventing infections, reducing serious disease or deaths in vaccinated individuals requires definition. In many parts of the world, HIV infection and other infections can synergize with the SARS-CoV-2 influencing COVID-19 management outcomes potentially influencing both pathogenesis of COVID (Karim F et al 2021;Nachega et al 2021b;Nachega et al 2021c).…”
Section: Major Knowledge Gaps On Voc Omicronmentioning
confidence: 99%
“…Two studies from South Africa demonstrated that HIV-1 is associated with suboptimal CD4 + T cells and humoral immune responses to SARS-CoV-2, especially in the absence of suppressive antiretroviral therapy [ 272 , 273 ]; and one US study showed that HIV-1 is associated with lower nAb titers after natural infection [ 274 ]. Immunosuppression due to the ineffectiveness of antiretroviral treatment and resistance to HIV-1 drugs leads to a violation of both cellular and adaptive humoral immunity, which prevents the elimination of SARS-CoV-2 [ 275 ].…”
Section: Covid-19 and Hiv-1mentioning
confidence: 99%
“…As mentioned earlier, no study so far has established any link between being HIV-1-infected and being more vulnerable to contracting COVID-19 ( 32 ). What is known though is that being infected with HIV-1 is a risk factor for developing severe COVID-19 ( 79 ) and for COVID-19 related mortality ( 33 35 ). Furthermore, a recent case report in South Africa revealed the development of over ten new SARS-CoV-2 variants in one individual who presented with untreated HIV-1 infection and had been co-infected with SARS-CoV-2 ( 80 ).…”
Section: Covid-19 In Hiv-1-infected Individualsmentioning
confidence: 99%
“…The pandemic will continue until further studies reveal the veritable correlates of protection against SARS-CoV-2 and/or the whole world is immunized, including those most vulnerable to severe COVID-19 such as those living with HIV-1. Waning vaccine-induced antibodies ( 95 ) and emerging new variants ( 54 , 55 , 79 ) will inadvertently prolong the period during which vaccine booster jabs and vaccines against VOC will be required.…”
Section: Challenges Aheadmentioning
confidence: 99%